ENGLISH TEACHER'S PERSONAL CHARACTERISTICS THAT MOTIVATE THE STUDENTS IN THE CLASSROOM: EFL STUDENTS' PERSPECTIVE - ., Luh Putu Ayu Surya Pratiwi; ., I Putu Ngurah Wage M, S.Pd.; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This research aimed to identify the EFL teacher’s personal characteristics that motivate the students in the classroom and to find out the students’ reasons of being motivated by their English teacher’s personal characteristics. The subjects of the study were 68 students of the eleventh grade of SMA Negeri 1 Negara in the academic year 2014/2015. This research was designed in the form of qualitative descriptive research. This research used focus group discussion as main data collection, observation and note taking as supporting data collection in collecting the data. The result of the study showed that there were six English teacher’s personal characteristics that motivated the students in the classroom namely having a sense of humor, demonstrating professional responsibility, effective rapport (being friendly, being respectful, and being kind), being patient, caring and being creative. A humorous teacher made the classroom environment cheerful; the students were enthusiastic in listening the lesson; and increase the students’ willingness to learn English. A friendly teacher made the students feel so close to the teacher which made them comfortable in learning English and brave to ask something related to the lesson. A creative teacher could entertain the students which made the students enthusiastic (not bored), interested, and fun during the lesson so the classroom environment would be pleasant and made the students remember the lesson longer and feel challenged to finish the assignment. A kind teacher made the students enjoy the study. A patient teacher made the students brave to ask something or share their opinion. A professional teacher made the students easier to catch the material and become more disciplined in the learning process. A caring teacher made the students feel secured and better understand the lesson. A respectful teacher made the students confident.keyword : EFL, motivation, personal characteristics